GENERATIVE AI-SUPPORTED FEEDBACK IN EFL WRITING (A SYSTEMATIC LITERATURE REVIEW) - Yetty Tri Putri (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
This study aims to systematically review the use of Generative Artificial Intelligence (GenAI)-supported feedback in English as a Foreign Language (EFL) writing. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines through the identification, screening, eligibility, and synthesis of relevant studies. Data were collected from peer-reviewed articles indexed in ERIC, Crossref, and major academic databases, resulting in 20 eligible empirical studies published between December 2022 and July 2026. The findings show that GenAI-supported feedback improves revision quality, grammatical accuracy, vocabulary, coherence, and learner engagement. However, teacher feedback remains essential for supporting higher-order writing skills, while combining AI and teacher feedback provides the most effective learning outcomes. Overall, GenAI serves as a valuable tool to support feedback and revision rather than replace teachers in EFL writing instruction.